Natura i charakterystyka bogów w mitologii - Bär , Silvio (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2020)
This article is intended for students and teachers of classical mythology. It gives an overview of the nature and the characteristics of the gods in Greek and Roman mythology, explaining what the Greek and Roman gods are and what they are not. Furthermore, the relationship between gods and humans in classical mythology is discussed.